ANALISIS KANDUNGAN ZAT PENGAWET BORAKS PADA JAJANAN SEKOLAH DI SDN SERUA INDAH 1 KOTA CIPUTAT - Santi, Apri Utami Parta (Universitas Muhammadiyah Jakarta, 2017)
This research is motivated by the proliferation of street food sellers who use harmful preservatives. Many snacks sellers in front of SDN Serua 1 be the reason researchers wanted to know whether the snacks contain preservatives borax. This type of research is descriptive laboratory. The study was conducted by interviewing sellers and doing a simple examination and laboratory with colorimetric method. The population in this study street food seller who trade outside the school fence SDN Serua 1. Snacks that have been analyzed in laboratory is negative, which means all food contains no preservatives borax. So snacks in front of SDN 1 Serua safe for consumption by the students and surrounding communities